IMPACT OF SOCIO-ECONOMIC FACTOR ON CHILD DEVELOPMENT AMONG URBAN POOR - A STUDY IN BANGALORE, INDIA - Stany D’Souza; Sheela A.M; Raja Jebasingh.D (European Scientific Journal, ESJ, 2013)
﻿﻿﻿﻿The study has been undertaken to document the nutritional status of school going children among Bangalore’s Urban Poor and to document the factors influencing it. The three anthropometric measures namely wasting, stunting and underweight is used to understand the level of malnutrition in children. The main focus of the study is to document the nutrition status of children from poor urban households through the anthropometric measures, to analyse the socio economic factors like gender and income and their impact on nutritional status. The data was collected from a sample of households drawn from Bangalore’s slums and was drawn using cluster sampling. Moderate levels of stunting is seen in majority of households and also across both gender, slightly higher with the female children and it was found predominant in small and large families across all categories of caste. The Gomez index measuring nutrition based on weight for age found small percentage of children with mild form of malnutrition across income and gender groups. Gomez analysis also found that with increase in family size the level of malnutrition, which is strengthened through the logistic regression. Wasting was also found at moderate levels in more than fifty percent of the households. logistic regression was used to analyse the factors influencing economic development revealed that the age of the child and family size were deterrent factors affect nutrition levels.